Adiabatic transfer for atomic interferometry. - Featonby, P; Summy, G; Martin, J; Wu, H; Zetie, K; Foot, C; Burnett, K (1996)
We have observed momentum transfer in cesium atoms using the process of adiabatic transfer between dark states. We have investigated the sensitivity of this process to Zeeman shifts and to the differences between the translational energies of the states involved. We have shown that, for a chosen velocity class, the resultant phase shifts of the magnetic substates can be canceled so a dark state is maintained. Two different laser polarization conligurations were used to perform the experiments: two circularly polarized beams or a linearly and a circulary polarized beam. Results for each are presented. Finally we discuss the relevance of our results to atomic interferometry and consider methods to minimize the possible phase shifts introduced in an atomic interferometer based upon adiabatic transfer.